Association of Oral Conditions with Quality of Working Life of Brazilian Police Officers - Raísa Silva de Araújo; Lorenna Mendes Temotéo Brandt; Alidianne Cabral Cavalcanti; Catarina Ribeiro Barros de Alencar; Alessandro Leite Cavalcanti (Universidad de Concepción., 2018)
Objective: To evaluate the impact on the quality of working life of Brazilian police officers with Temporomandibular Disorders (TMD). Materials and Methods: The sample consisted of 52 subjects and information was collected through the WHOQOL-BREF questionnaire and the Fonseca Anamnesis Index to evaluate the level of temporomandibular disorder (TMD), followed by clinical examination to determine the experience of dental caries, by means of the DMFT index. Descriptive and inferential statistical analysis (chi-square test) was performed through the Statistical Package for the Social Sciences software. The significance level was 5%. Results: The sample was predominantly composed of males (94.2%) with a mean age of 39.4 years (±9.4) and mean service length of 17.3 years (±11.0). The mean DMFT index value was 15.6 (±6.1), especially the "filled" component, whose mean was 12.1 (±5.4). The presence of TMD was found in 67.3% of the sample, of predominating mild degree (91.4%). Quality of working life (QWL) was classified as unsatisfactory/neutral by 57.7% of participants. There was a statistically significant association between QWL and presence of TMD (p<0.05); however, there was no association between DMFT index and the presence of TMD (p>0.05). Conclusion: Although military police officers presented a high mean DMFT index value, there was highest prevalence of the "filled" component, evidencing a past experience of caries and evidencing that this population has access to oral health services. The occurrence of TMD was high, predominating the mild degree, and there was an association with QWL.